IDENTIFIKASI PERUBAHAN KERAPATAN VEGETASI DI KAWASAN HUTAN DENGAN TUJUAN KHUSUS UNIVERSITAS LAMBUNG MANGKURAT - Sitinjak, Petrus; Asy'ari, Mufidah; Udiansyah, Udiansyah (Universitas Lambung Mangkurat, 2024)
The Forest Area with a Special Purpose of Lambung Mangkurat University has an area of approximately 2000 Ha, divided into 2 areas, namely Bukit Babaris and Bukit Waringin. Identification of changes in land cover and vegetation density has never been carried out, especially in the Babaris mountain area (1,617 hectares). This study aims to compare the results of the accuracy of the Maximum Likelihood Classification (MLC) method with the Normalized Different Vegetation Index (NDVI) method in identifying vegetation density from 2018 to 2022. The results of the accuracy test for the vegetation density method using the confusion matrix show that the Overall Accuracy value of the MLC method is low lower, namely 92.5%, and the NDVI method 93.75%. It can be concluded that the NDVI method is more sensitive in detecting vegetation than the MLC method. Factors that affect the inaccuracy of the MLC method depend on the accuracy and the number of class class training samples taken. Based on the results of the interpretation of density changes from the two methods, from 2018 to 2022 the area of vegetation classes tends to increase and looks fluctuating. The area of change in vegetation density in the MLC method of the non-vegetation classification class is relatively stable at over 9 ha/year, although the classification class rarely dominates over the year. Changes in the density of non-vegetation class vegetation in the NDVI method tend to decrease significantly in 2020 and 2021. Based on the two most accurate methods obtained by the NDVI method, that there is an increase in vegetation density in the KHDTK ULM area of the Babaris hill.